Engineering rock mechanics : part 2: illustrative worked examples - Harrison, John P. (Pergamon, 2000)
Engineering Rock Mechanics Part II: Illustrative Worked Examples can be used as an independent book or alternatively it complements an earlier publication called Engineering Rock Mechanics: An Introduction to the Principles by the same authors. It contains illustrative worked examples of engineering rock mechanics in action as the subject applies to civil, mining, petroleum and environmental engineering. The book covers the necessary understanding and the key techniques supporting the rock engineering design of structural foundations, dams, rock slopes, wellbores, tunnels, caverns, hydroelectric schemes and mines. There is a question and worked answer presentation with the question and answer sets collated into twenty chapters which match the subject matter of the first book.